Technological Foundations for Drilling Rapal Deposits Under Difficult Conditions - Ergash Safarovich Mirzayev (Zien Journals, 2022)
The article discusses the difficulties of drilling salt deposits, their prevention and elimination, the chemicals used, the requirements for the drilling fluid, its preparation, water permeability, density, viscosity, static shear parameters and lubricants, as well as the definition of filtration parameters
Keywords: halogen; syneclise; tectonics; geophysical survey